Long-chain polyunsaturated fatty acids regulation of PPARs, signaling: Relationship to tissue development and aging. (November 2016) - Echeverría, Francisca; Ortiz, Macarena; Valenzuela, Rodrigo; Videla, Luis A.
Abstract: Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors that function as ligand-dependent transcription factors that can be activated by different types of fatty acids (FAs). Three isoforms of PPARs have been identify, namely, PPARα, PPARβ/δ, and PPARγ, which are able to bind long-chain polyunsaturated FAs (LCPUFAs), n-3 LCPUFAs being bound with greater affinity to achieve activation. FA binding induces a conformational change of the nuclear receptors, triggering the transcription of specific genes including those encoding for various metabolic and cellular processes such as FA β-oxidation and adipogenesis, thus representing key mediators of lipid homeostasis. In addition, PPARs have important roles during placental, embryonal, and fetal development, and in the regulation of processes related to aging comprising oxidative stress, inflammation, and neuroprotection. The aim of this review was to assess the role of FAs as PPARs ligands, in terms of their main functions associated with FA metabolism and their relevance in the prevention and treatment of related pathologies during human life span. Highlights: PPARs are nuclear receptors that function as ligand-dependent transcription factors that can be activated by different types of fatty acids. PPARs are able to bind LCPUFAs, and n-3 LCPUFAs have greater affinity to achieve activation of PPARs. PPARs have important roles during development and in the regulation of processes related to aging. N-3 LCPUFAs are PPARs ligands and these interactions is important in different pathologies during human life.